Peningkatan Kompetensi Guru Melalui Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Inovatif Berbasis Pembelajaran Daring - Ratna Widyastuti; Abidatul Izzah; Rinanza Zulmy Alhamri; Benni Agung Nugroho; Ellya Nurfarida (P2M Polinema, 2021)
The high interest of the students has motivated the teachers at SDN Dermo 1 to improve the quality of learning. Therefore, they initiate to create a learning media innovations such as manipulative media and computer media. However, building a learning innovations with computers-based was not accompanied by the abilities. To solve this problem, we hold community service activities that aimed to improve their capability in developing innovations by holding outreach on mathematics learning methods and training on implementing computer applications. The last step in this program is assistance in developing and implementing computer learning media in online course. Further, the Community Service Program named